ANALISIS IMPLEMENTASI SISTEM INFORMASI AKUNTANSI DENGAN MENGGUNAKAN SOFTWARE AKUNTANSI PADA PT CAHAYA PULAU PURA - Erikka, Erikka; Natalia, Erni Yanti (SCIENTIA JOURNAL, 2021)
The purpose of this research is to implement accounting information system using MYOB Accounting and to analyze constraints in the implementation of accounting information system using accounting software at PT Cahaya Pulau Pura. The method used in this research is descriptive qualitative analysis method with observative data collection, interviews, as well as documentation obtained from the companies studied. The result of the research is that the accounting system in MYOB is more adequate than Microsoft Excel because it has special features in processing data. The conclusion is that Microsoft Excel cannot be used to present financial reports, because it does not have special features and also the data processing process using Microsoft Excel manually, there are still many weaknesses and it causes the data processing to be long and inefficient while MYOB software has many useful features for PT Cahaya Pulau Pura in processing financial report data, making it easier for the financial department to manage and make decisions.